Environmental policy in the European Community (Luxembourg : Office for Official Publications of the European Communities(OPOCE), 1990)
The white paper on completing the single European market attaches great importance to environment policy because environmental problems may become even more acute through the 1992 objectives being achieved and as a result of the expected acceleration in economic growth.
aia 19/07/16
Loans
Keywords: Environmental policy; Europe - European Economic Community countries